2011
DOI: 10.1017/s0022029911000094
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for analysis of proteolysis by plasmin in milk

Abstract: Sensitive methods that are currently used to monitor proteolysis by plasmin in milk are limited due to their high cost and lack of standardisation for quality assurance in the various dairy laboratories. In this study, four methods, trinitrobenzene sulphonic acid (TNBS), reverse phase high pressure liquid chromatography (RP-HPLC), gel electrophoresis and fluorescamine, were selected to assess their suitability for the detection of proteolysis in milk by plasmin. Commercial UHT milk was incubated with plasmin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Plasmin produces peptides that are soluble at pH 4.6 but not in 4% TCA, whereas exogenous enzymes produce peptides that are soluble under both conditions. Thus a sample with a high NCN but with a low NPN is likely to be hydrolyzed by plasmin, whereas a sample with high NCN and NPN is likely to be proteolyzed by exogenous enzymes or a combination of exogenous enzymes and plasmin (Chove et al., ; Datta & Deeth, ).…”
Section: Age Gelationmentioning
confidence: 99%
“…Plasmin produces peptides that are soluble at pH 4.6 but not in 4% TCA, whereas exogenous enzymes produce peptides that are soluble under both conditions. Thus a sample with a high NCN but with a low NPN is likely to be hydrolyzed by plasmin, whereas a sample with high NCN and NPN is likely to be proteolyzed by exogenous enzymes or a combination of exogenous enzymes and plasmin (Chove et al., ; Datta & Deeth, ).…”
Section: Age Gelationmentioning
confidence: 99%
“…There was a poor correlation between the pH reduction caused by acid addition and that resulting from increasing temperature. Sediment formation was related to pH change at high temperature (Lewis, 2011). It was concluded from one study that the nature of the calcium-and heat-induced gelation or coagulation of milk is influenced, and can be manipulated, by a combination of factors including ionic calcium concentration, temperature, milk pH and milk solids level (Deeth & Lewis, 2015).…”
Section: It Is Obvious Formmentioning
confidence: 99%
“…Datta and Deeth (2001) stated that although SHMP inhibited gelation, it did not affect proteolysis. It was documented that addition of 0.15 mg/L plasmin caused gelation of UHT milk in 90 days (Kohlmann et al, 1991), indicating the significance of minor proteolysis by plasmin prior to gelation (Chove et al, 2011). It was also revealed that neither gelation nor proteolysis (9 months at 20 °C ) was observed in a study where serine protease inhibitors were added to UHT skim milk to inhibit plasmin activity, implicating the role of plasmin in proteolysis preceding gelation (De Koning et al, 1985).…”
Section: Effect Of Proteolysis Of Uht Milk At 25 °Cmentioning
confidence: 99%
“…In a study by Chove et al, (2011) analysis of proteolysis by plasmin enzyme on day 7, showed completely disappearance of both the α-and β-casein bands, indicating extensive proteolysis on these caseins. Microbial enzymes have been reported to show preference to hydrolyse κ-casein, which is usually found on the surface of the casein with the formation of para-κ-casein (Snoeren & Van Riel, 1979), followed by extensive hydrolysis which is non-specific (Law et al, 1977).…”
Section: Proteolysis Caused By Pseudomonas Fluorescensmentioning
confidence: 99%